1993
DOI: 10.1088/0022-3727/26/12/012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nitrogen on the oxygen dissociation in a DC discharge

Abstract: The effect of the addition of molecular nitrogen on the oxygen dissociation is investigated in a low pressure gas discharge. The dissociation efficiency is measured as a function of N2 concentration, for a total pressure ranging from 0.4 to 3 Torr in discharge tubes with diameter between 6 and 21 mm. The concentration of O atoms is obtained by the NO+O chemiluminescent reaction. The authors show that for a few percent of nitrogen the oxygen dissociation degree varies by a factor of 1.5-10 depending on the nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 17 publications
1
16
0
1
Order By: Relevance
“…The microwave power is held at 40 W and an oxygen flow of 5 sccm is used in this study. Moreover, in order to increase the O atom flux reaching treated samples, an admixture of 0.2 sccm nitrogen is used, which drastically enhances the dissociation degree of oxygen due to a decrease in a wall diffusion loss of O atoms 22, 23. Moreover, it has to be noted that S‐bend shape of the connecting tube avoids direct line‐of‐sight from the microwave plasma to the sample eliminating the exposure of the sample to possible UV and VUV radiation, which is connected with production of excited NO molecules and which can contribute to the proteins removal.…”
Section: Experimental Partmentioning
confidence: 99%
“…The microwave power is held at 40 W and an oxygen flow of 5 sccm is used in this study. Moreover, in order to increase the O atom flux reaching treated samples, an admixture of 0.2 sccm nitrogen is used, which drastically enhances the dissociation degree of oxygen due to a decrease in a wall diffusion loss of O atoms 22, 23. Moreover, it has to be noted that S‐bend shape of the connecting tube avoids direct line‐of‐sight from the microwave plasma to the sample eliminating the exposure of the sample to possible UV and VUV radiation, which is connected with production of excited NO molecules and which can contribute to the proteins removal.…”
Section: Experimental Partmentioning
confidence: 99%
“…Using Eqs. (10)(11)(12)(13)(14)(15)(16)(17) and (19)(20)(21)(22), Eqs. (32)(33)(34)(35) can be rewritten in the form…”
Section: Kinetic Model For Surface Processesmentioning
confidence: 99%
“…The interpretation of the Ref. [8][9][10][11][12] experiments requires the development of a kinetic theory for surface processes taking into account different kinds of atoms and surface diffusion of physisorbed atoms. Moreover, because of experimental evidence for the dependence of the probabilities°M on the relative concentrations of different kinds of gas-phase atoms, the development of a self-consistentmodel for gas-phase and surface kinetic processes in low-pressure nonequilibrium plasma becomes important and necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors [1,2,3,4,5] demonstrated that even a small admixture can dramatically change the dissociation of the gas. This phenomenon is generally supposed to be caused by one or more of the following effects: change of reduced electric field E/N in the discharge, various homogeneous reactions or by decrease of the wall recombination coefficient due to heterogeneous reactions.…”
Section: Introductionmentioning
confidence: 99%